2021
DOI: 10.3928/01477447-20210414-09
|View full text |Cite
|
Sign up to set email alerts
|

Race Predicts Unsuccessful Healing of Osteochondritis Dissecans in the Pediatric Knee

Abstract: The purpose of this study was to evaluate the effect of race, insurance status, and socioeconomic status on successful or unsuccessful healing of osteochondritis dissecans (OCD) lesions in the pediatric knee. The authors retrospectively reviewed patients younger than 18 years who were treated for a knee OCD lesion between 2006 and 2017. Patients were required to have at least 6 months of clinical and radiographic follow-up to be included, unless complete healing was achieved sooner. The primary outcome of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In contrast, a few studies have shown racial disparities in orthopedic care for pediatric patients [9,11]. Malyavko et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a few studies have shown racial disparities in orthopedic care for pediatric patients [9,11]. Malyavko et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Patel et al . aimed to evaluate whether race influences the healing of osteochondritis dissecans (OCD) lesions in pediatric patients [9]. After multivariate analyses, African American children with OCD were found to have 6.7 times higher odds of unsuccessful healing than Caucasian children [9].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Patel et al investigated the healing pattern of osteochondritis dissecans lesions in pediatric knees. They found that black patients had 6.7 times greater odds of unsuccessful healing when compared to the White patient cohort [ 15 ]. Another study by Kulaylat et al looked at factors impacting the transfer of pediatric trauma patients from adult trauma centers to pediatric trauma centers and found that there was an increased rate of interfacility transfer for uninsured pediatric patients and non-White patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Identification of disparities in access, quality, or outcomes of care provides opportunities for intervention on behalf of the populations experiencing dissimilar care or outcomes. There is a statistical significance that, even when adjusting for age, sex, sports participation, lesion size and stability, and surgical versus nonsurgical treatment, impacts the rate of healing 2 . The study design did not mention the difference between these factors, which can affect the data that was received.…”
mentioning
confidence: 99%
“…There is a statistical significance that, even when adjusting for age, sex, sports participation, lesion size and stability, and surgical versus nonsurgical treatment, impacts the rate of healing. 2 The study design did not mention the difference between these factors, which can affect the data that was received.…”
mentioning
confidence: 99%